O Conselho Nacional de Política Criminal e Penitenciária e a dignidade dos apenados capixabas: uma abordagem a partir da criminologia crítica - Marques, Fabiano Lepre (2012)
The following monographic work, which research is included on the research line “Democracy, Citizenship, and Fundamental Rights” of the Faculdade de Direito de Vitória Master of Laws Program, analyses the role played by the National Council of Criminal and Penitentiary Policies and whether it is determinant for the effectiveness of the rights and the dignity of prisoners. There are faced thus three questions. The first question demonstrates the prisoner’s situation within the capixaba criminal execution system and detaches that such condition has not changed too much after the Council intervention. Setting such question allows to direct the critics from a theoretical analysis, in which are utilized some of the appointments made by Bourdieu, Wacquant, Bauman, Žižek, Jock Young, Garland, Jakobs, Baratta, Gabriel Ignacio Anitua, and Thiago Fabres de Carvalho, demonstrating that the functioning of the capixaba penitentiary system is not a fortuity. Finally, the third question is a finding obtained since the previous developed dialectic that the Council performance must be enhanced for that the prisoner’s fundamental rights be concretized and respected, promoting, then, their dignity as human beings; or else, it makes no sense the existence of such Council.